2017
DOI: 10.29269/pbb2017.v1i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Infection: The Common Cause of Human Food Poisoning

Abstract: Salmonellosis infection is caused by a Salmonella bacteria which was first found by Soholerin in 1839, and it isolated by Karl Eberth in 1880 from the mesenteric lymph nodes and spleen of a person died from typhoid fever. Salmonella was cultured by Georg Theodor Gaffky in 1884 and by Salmon and Smith from pigs which had died of hog cholera. The disease can affect all species of domestic animals and man, but young, aged, debilitated, stressed, pregnant, and lactating animals and humans are more susceptible, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The presence of Salmonella in this study calls for concern as this organism is the common cause of human food poisoning, and salmonellosis can affect all species of domestic animals and man. It is important to draw to our attention that the young, aged, stressed, debilitated and pregnant individuals are more susceptible while the immunosuppressed and those suffering from malnutrition are at risk for salmonella infection [19].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of Salmonella in this study calls for concern as this organism is the common cause of human food poisoning, and salmonellosis can affect all species of domestic animals and man. It is important to draw to our attention that the young, aged, stressed, debilitated and pregnant individuals are more susceptible while the immunosuppressed and those suffering from malnutrition are at risk for salmonella infection [19].…”
Section: Resultsmentioning
confidence: 99%
“…and Salmonella sp. to be present in any food product because these pathogens are responsible for food-borne diseases [20,21]. This study has shown that S. aureus and Bacillus sp.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of Enterobacteriaceae shows that a failure occurred during processing and their absence indicates that improper hygienic conditions were maintained during the food manufacturing process. Enterobacteriaceae include many pathogens especially Salmonella which is found in meat and its products (especially poultry) and causes food poisoning (Rahman and Othman 2017). Enterobacteriaceae produce biogenic amines cadaverine, histamine, and tyramine in.…”
Section: Discussionmentioning
confidence: 99%